Species of the genus Anicetus Howard (Hymenoptera: Encyrtidae) from the New World - Trjapitzin, Vladimir A.; Ruíz Cancino, Enrique (Instituto de Ecología, A.C., 2009)
Two new species from Mexico, Anicetus myartsevae sp. nov. from the State of Tamaulipas and A. villarreali sp. nov. from the State of Nuevo León, are described. Taxonomical characteristics of Anicetus, the key to females of seven species of this genus present in the New World, and a synopsis of the American species with data on geographic distribution, hosts and biology, are included.